Os (des)caminhos das águas do Rio Poxim no bairro Jabotiana em Aracaju: o olhar geoambiental do discente - Araujo, Claudionete Candia (2018)
The Jabotiana neighborhhood has become target of real estate speculation whose expansion has reached areas nearby the Poxim River. These areas, which in the past were occupied by the riverside population, gave rise to residences and condominiums that changed the local landscape. The school community and the people who live around the river have been suffering with the reflexes of this occupation, because beside the river pollution, they suffer with frequente floods that enter the houses causing many financial, socioenviromental and emotional problems. The research aims to analyse the (mis)paths of the Poxim River water form the Geoenvironmental perspective from the first grade students of high school of the Joaquim Vieira Sobral School, at the Jabotiana neighborhood, at Aracaju/Sergipe. The research was carried out based on: bibliographical and documentary survey; application of a diagnostic questionnaire with the students involved; elaboration, application and analysis of the Intervencion Project entitled “Mobilization for Poxim River Conservation: na interdisciplinar approach” which involved: field class around school area; dialogue of knowledge between students and residentes; pedagogical workshop; Ecologic walk; mobilization for the conservation of the Poxim Rver; development and aplication of the geoenvironmental kit, and, completion of the intervention Project. The dialogue of knowledge through interdisciplinarity, enabled the students, to recognize themselves as protagonists of their own story, and made them feel estimulated to search for improvements for the neighborhood. Therefore, the construction and preparation of the Geoenvironmental Kit, supported by the relationsh between theory and practice, it was possible to instigate the critical and reflective Geo-environmental view of students about sócio-environmental problems beyond school walls, thus contributing to their formation citizen.